DAKWAH KULTURAL KGPH PUGER MENGATASI RADIKALISME KASUNANAN SURAKARTA HADININGRAT - Halim, Abd (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2016)
Radicalism are mostly based in the region of Surakarta Sultanate is the effect of the configuration of a plural society that loses role models. The functionalism point of view is used to perform the reading of cultural dakwah being carried out by Kanjeng Gusti Pangeran Haryo (KGPH) Puger in an effort to reduce radical teachings. The king and the palace as a symbol of center cultural power is responsible for returned as an ideal figure, which is acceptable to all groups and streams, which are able to bring unity in diversity. Cultural treasures, glory records as the history of the palace, the values of locality (local wisdoms) is the existing capital, and waiting to be applied. Cultural dakwah already displayed in their history to be a reference that Muslims in the Surakarta palace once lived in an era of splendor, without anarchism and without radicalism